A method for modifying the surface of magnesium negative electrode of magnesium-air battery
By modifying the bioceramic film layer on the surface of the magnesium negative electrode of the magnesium air battery and using calcium biphosphate dihydrate to form a protective film, the problem of self-corrosion of the magnesium negative electrode is solved, and the energy density and life of the battery are significantly improved.
Patent Information
- Application Number
- CN202310308167.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-03-27
AI Technical Summary
The magnesium negative electrode in magnesium air battery has severe self-corrosion in the neutral electrolyte, which leads to a far difference in the actual specific energy from the theoretical value. The main reasons are the hydrogen evolution reaction and the negative difference effect.
By modifying the bioceramic film layer on the magnesium negative electrode surface of the magnesium air battery, calcium hydrogen phosphate dihydrate is used as the main component to form a protective film to inhibit hydrogen evolution corrosion.
It effectively suppresses the hydrogen evolution phenomenon on the surface of the magnesium negative electrode, greatly improves the energy density of the magnesium air battery, avoids the "cluster effect", extends the battery life, and improves the stability of the discharge voltage.
Smart Images

Figure CN116356305B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium-air batteries, and in particular relates to a method for modifying the surface of a magnesium negative electrode of a magnesium-air battery. Background Art
[0002] Metal-air batteries use oxygen in the air as the positive electrode active material and metal (lithium, zinc, magnesium or aluminum, etc.) as the negative electrode active material. Oxygen passes through the gas diffusion electrode to the gas-solid-liquid three-phase interface and is electrochemically catalytically reduced. At the same time, the metal negative electrode undergoes an oxidation reaction to release electrical energy. In theory, air can provide an unlimited supply of positive electrode reaction active materials for metal-air batteries. Magnesium is one of the most abundant light metal elements on earth, with a density of 1.74g / cm 3 , with an abundance of 2% in the earth's crust, making it the eighth most abundant element. Magnesium, as a negative electrode, is less active than lithium, and the safety issues encountered when using magnesium are significantly fewer. Magnesium can be used in aqueous electrolyte batteries. Compared with aluminum and zinc, magnesium has a lower standard electrode potential (-2.37V). Magnesium also has a mass specific capacity of 2205Ah / kg, which is only less than lithium (3680Ah / kg) and aluminum (2980Ah / kg); its volume specific capacity is higher than that of lithium (3833Ah / L for magnesium and 2062Ah / L for lithium), which is very advantageous in cases where installation space is limited (such as mobile devices and electric vehicles). In aqueous electrolytes, the theoretical specific energy density of the reaction between magnesium and oxygen (2846Wh / kg) far exceeds that of zinc-air batteries (1086Wh / kg); the theoretical operating voltage is 3.10V, which is higher than that of zinc-air batteries (1.65V). Therefore, magnesium-air batteries have the advantages of high theoretical voltage, high specific capacity, light weight, low cost, and no pollution. At present, magnesium-air batteries are mainly used in small, lightweight portable power systems, emergency lights and emergency power backup systems, as well as lighthouses and other submarine instruments, monitoring equipment and buoys. Magnesium-air batteries have also been used in the military field to supply energy for some military detectors (Yang Weiqian, Yang Shaohua, Sun Gongquan, Xin Qin, The Development and Application of Magnesium Fuel Cells, Power Technology, 2005, 29, 182-186).
[0003] During the discharge process of magnesium-air batteries, the magnesium negative electrode is oxidized to produce magnesium ions, and electrons flow into the positive electrode through an external circuit. At the positive end, oxygen in the air diffuses to the three-phase interface through the air, and the electrons are electrochemically catalytically reduced, reacting with water to produce hydroxide. At present, there are still many problems with magnesium-air batteries, mainly because the magnesium negative electrode has serious self-corrosion in neutral electrolytes, which makes the actual specific energy far from the theoretical value. The main reasons for the above problems are "hydrogen evolution reaction" and "negative difference effect". Therefore, finding magnesium negative electrode materials with high utilization rate and high electrochemical activity is an important hot spot and difficult problem in the field of magnesium-air battery research. The key is to reduce hydrogen evolution corrosion and agglomeration effect, and solve the contradiction between activation and passivation. In order to solve the above problems, many researchers have studied magnesium negative electrodes from different directions such as microstructure design, magnesium alloy research and development, negative electrode surface modification, and improvement of processing state and heat treatment methods, and have made many important progress.
[0004] Modifying the surface of the magnesium anode in contact with the electrolyte is a strategy to improve the performance of the magnesium anode. The anode / electrolyte interface determines the performance and life of the battery and has been the subject of many studies. Surface modification includes surface film modification and surface mechanical modification. Surface film modification refers to the use of micro-arc oxidation, laser surface melting, sol-gel, chemical conversion film, electrochemical deposition, liquid phase deposition and other methods to form a protective film layer on the contact surface between the anode and the electrolyte. Surface mechanical modification refers to improving the mechanical strength integrity of the magnesium alloy surface through methods such as shot peening, extrusion, polishing, milling and ultrasonic rolling, thereby improving the utilization rate of the magnesium anode. Summary of the invention
[0005] In order to avoid or reduce the serious hydrogen evolution corrosion of the magnesium negative electrode of the existing magnesium-air battery, resulting in low negative electrode utilization; severe hydrogen evolution corrosion causes a "lump effect" on the surface of the magnesium negative electrode, and a large amount of magnesium metal falls off in blocks; Mg(OH)2 products are continuously deposited on the electrode surface to form a denser passivation film, which affects the activation and dissolution of the magnesium negative electrode, aggravates the charge accumulation, and keeps the magnesium negative electrode at a higher polarization voltage, which makes the discharge voltage of the magnesium-air battery at a high current density lower, causing the actual voltage of the magnesium-air battery to be lower than the theoretical voltage. The present invention provides a surface modification method for the magnesium negative electrode of a magnesium-air battery, and in particular provides a magnesium negative electrode modified with a bioceramic film layer whose main component is dihydrate calcium hydrogen phosphate.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for modifying the surface of a magnesium negative electrode of a magnesium-air battery, comprising the following steps:
[0008] S1: Cut the magnesium sheet into a number of electrode sheets of a certain size, polish them with sandpaper, then wash them with distilled water, and finally ultrasonically clean them in an organic solvent. After drying, they are used as magnesium negative electrodes of magnesium-air batteries.
[0009] S2: The surface of the magnesium negative electrode was polished and cleaned at room temperature. The magnesium negative electrode was immersed in a supersaturated solution of Ca(OH)2. 2+ Pre-adsorb, remove, and wash with deionized water;
[0010] S3: Soaking the pretreated magnesium negative electrode in a deposition solution (a mixed solution of calcium salt and dihydrogen phosphate) at room temperature to obtain a magnesium negative electrode modified with a bioceramic film layer whose main component is calcium hydrogen phosphate dihydrate, taking it out, washing it with deionized water, vacuum drying it, and sealing and packaging it for later use;
[0011] Preferably, the size of the magnesium negative electrode after cutting in step S1 is 30 mm×60 mm×0.5 mm;
[0012] Preferably, the model of the water-abrasive sandpaper used in step S1 is selected from 120#, 360#, 600#, and 1200#;
[0013] Preferably, the organic solvent used in step S1 is a volatile solvent such as anhydrous ethanol or acetone;
[0014] Preferably, the magnesium sheet used in step S1 is selected from a pure magnesium sheet and a magnesium alloy sheet, such as a WA111 magnesium alloy sheet and an AZ31 magnesium alloy sheet.
[0015] Furthermore, in step S3, a mixed solution of calcium salt and dihydrogen phosphate can be used as the electrolyte, the treated magnesium negative electrode is used as the cathode, and the anode is a saturated KCl electrode. The electrodeposition is carried out in a constant voltage mode, the voltage is set to 3V, and the deposition is carried out at room temperature for 4 hours to obtain a magnesium negative electrode modified with a bioceramic film layer whose components are dihydrate calcium hydrogen phosphate and a small amount of calcium phosphate.
[0016] Preferably, the calcium salt of the present invention can be selected from Ca(NO3)2, CaCl2;
[0017] Preferably, the dihydrogen phosphate of the present invention is selected from KH2PO4, NH4H2PO4;
[0018] Preferably, the concentration range of the calcium salt of the present invention is 0.03 to 0.08 mol / L;
[0019] Preferably, the concentration range of the dihydrogen phosphate of the present invention is 0.015 to 0.05 mol / L.
[0020] Performance Test:
[0021] The present invention assembles a magnesium-air battery by assembling a magnesium negative electrode modified by a bioceramic film layer whose main component is calcium hydrogen phosphate dihydrate and whose surface is modified by solution deposition or electrochemical deposition, and an air positive electrode with a 3.5wt% NaCl aqueous electrolyte and a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization and hydrogen evolution corrosion tests are performed.
[0022] A magnesium negative electrode modified with a bioceramic film layer whose main component is calcium hydrogen phosphate dihydrate and whose surface has been modified by solution deposition or electrochemical deposition is assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte, and an AC impedance test is performed after standing for 1 hour.
[0023] Beneficial effects of the present invention:
[0024] 1. The main innovation of the present invention is to modify the surface of the magnesium negative electrode of the magnesium air battery to form a protective layer on the surface of the magnesium negative electrode, inhibit hydrogen evolution, and improve the utilization rate of the negative electrode. The formed bioceramic film layer provides a certain hydrophobicity to the surface of the magnesium alloy film layer. The captured hydrogen will form a gas film in these uniformly staggered fine structures, making it difficult for water to contact magnesium metal for a long time, thereby achieving the purpose of slowing down hydrogen evolution corrosion. The hydrogen evolution phenomenon on the surface of the magnesium negative electrode is effectively suppressed, greatly improving the energy density of the magnesium air battery.
[0025] 2. The protective film formed by the method of the present invention is uniform and dense, and can allow Mg 2+ By avoiding the "clump effect". The film layer is composed of needle-like crystals of various orientations and cross-staggered with a length and width of 10 to 60 μm and a thickness of nanometers. These crystals show a multi-level interlocking and superimposed upward growth trend. This interlocking and interweaving growth of crystals can improve the bonding strength of the coating and form a uniform and dense porous bioceramic film layer, avoiding the occurrence of the "clump effect". It further improves the utilization rate of the magnesium negative electrode and prolongs the battery life.
[0026] 3. The special surface morphology of the protective film formed by the method of the present invention makes the passivation layer loose and easy to fall off. The porous microstructure on the surface of the bioceramic film layer formed can make the surface product of the magnesium alloy loose and porous, easy to fall off, and unable to form a complete and dense passivation film. The discharge voltage and discharge stability of the battery are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The photos are of the magnesium negative electrodes of the magnesium-air batteries in Comparative Example 1-3 and Example 1-3 after being discharged for 12 hours;
[0028] Figure 2The optical photograph (a) and scanning electron microscope image (b) of the magnesium negative electrode in Example 2, and the scanning electron microscope image of the magnesium negative electrode of the magnesium-air battery in Example 2 (c) and Comparative Example 2 (d) after discharge for 12 hours;
[0029] Figure 3 The AC impedance diagrams of the magnesium electrodes in Comparative Example 1-3 and Example 1-3 after being immersed in 3.5wt% NaCl aqueous electrolyte;
[0030] Figure 4 It is a graph of the hydrogen evolution rate of the magnesium negative electrode of the magnesium-air battery in Comparative Example 1-4 and Example 1-3 when discharged for 12 hours.
[0031] Figure 5 The discharge specific capacity and negative electrode utilization of the magnesium-air battery in Comparative Example 2 and Example 2 at different current densities for 12 hours. DETAILED DESCRIPTION
[0032] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0033] Example 1
[0034] A method for modifying the surface of a pure magnesium negative electrode of a magnesium-air battery comprises the following steps:
[0035] S1, cut the pure magnesium sheet into several electrode sheets of 30 mm × 60 mm × 0.5 mm, polish them with water-abrasive sandpaper (120#, 360#, 600#, 1200#) in sequence, then wash them with distilled water, and finally ultrasonically clean them in anhydrous ethanol for 10 min, and use them as magnesium negative electrodes of magnesium-air batteries after drying with cold air;
[0036] S2, the surface of the pure magnesium negative electrode was polished and cleaned and immersed in a supersaturated solution of Ca(OH)2 for 12 h at room temperature. 2+ Pre-adsorb, remove, and wash with deionized water;
[0037] S3, soaking the pretreated pure magnesium negative electrode in a deposition solution (a mixed solution of 0.042 mol / L Ca(NO3)2 and 0.025 mol / L NH4H2PO4) at room temperature for 24 h to obtain a magnesium negative electrode modified with a bioceramic film layer composed of calcium hydrogen phosphate dihydrate, taking it out, washing it with deionized water, vacuum drying it, and sealing and packaging it for later use;
[0038] The surface-modified pure magnesium negative electrode was assembled into a magnesium metal air battery with a 3.5wt% NaCl aqueous electrolyte and an air positive electrode with a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization, and hydrogen evolution corrosion tests were performed.
[0039] The surface-modified pure magnesium negative electrode was used as the working electrode, and was assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte. After standing for 1 hour, an AC impedance test was performed.
[0040] Comparative Example 1:
[0041] A pure magnesium negative electrode without surface modification was assembled into a magnesium metal air battery with a 3.5wt% NaCl aqueous electrolyte and an air positive electrode with a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization and hydrogen evolution corrosion tests were performed.
[0042] A pure magnesium negative electrode without surface modification was assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte, and an AC impedance test was performed after standing for 1 hour.
[0043] Embodiment 2:
[0044] A method for modifying the surface of a WA111 magnesium alloy negative electrode of a magnesium-air battery comprises the following steps:
[0045] S1, cutting the WA111 magnesium alloy sheet into several electrode sheets of 30 mm × 60 mm × 0.5 mm, polishing them with water-abrasive sandpaper (120#, 360#, 600#, 1200#) in sequence, then washing them with distilled water, and finally ultrasonically cleaning them in anhydrous ethanol for 10 min, and drying them with cold air to use them as magnesium negative electrodes of magnesium-air batteries;
[0046] S2, the surface of the WA111 magnesium alloy negative electrode was polished and cleaned and immersed in a supersaturated solution of Ca(OH)2 for 12 h at room temperature. 2+ Pre-adsorb, remove, and wash with deionized water;
[0047] S3, soaking the pretreated WA111 magnesium alloy negative electrode in a deposition solution (a mixed solution of 0.05 mol / L CaCl2 and 0.03 mol / L KH2PO4) at room temperature for 24 h to obtain a magnesium negative electrode modified with a bioceramic film layer composed of dihydrate calcium phosphate and a small amount of monocalcium phosphate, taking it out, washing it with deionized water, vacuum drying it, and sealing it for later use;
[0048] The surface-modified WA111 magnesium alloy negative electrode was assembled into a magnesium metal-air battery with a 3.5wt% NaCl aqueous electrolyte and an air positive electrode with a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization, and hydrogen evolution corrosion tests were performed.
[0049] The surface-modified WA111 magnesium alloy electrode was assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte, and an AC impedance test was performed after standing for 1 hour.
[0050] Comparative Example 2
[0051] The WA111 magnesium alloy negative electrode without surface modification was assembled into a magnesium metal air battery with a 3.5wt% NaCl aqueous electrolyte and an air positive electrode with a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization and hydrogen evolution corrosion tests were performed.
[0052] A WA111 magnesium alloy electrode without surface modification was assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte, and an AC impedance test was performed after standing for 1 hour.
[0053] Embodiment 3:
[0054] A method for modifying the surface of an AZ31 magnesium alloy negative electrode of a magnesium-air battery comprises the following steps:
[0055] S1, cutting the AZ31 magnesium alloy sheet into several electrode sheets of 30 mm × 60 mm × 0.5 mm, polishing them with water-abrasive sandpaper (120#, 360#, 600#, 1200#) in sequence, then washing them with distilled water, and finally ultrasonically cleaning them in anhydrous ethanol for 10 min, and then drying them with cold air to use them as magnesium negative electrodes of magnesium-air batteries;
[0056] S2, the surface of the AZ31 magnesium alloy negative electrode sheet that has been polished and cleaned is immersed in a supersaturated solution of Ca(OH)2 for 12 h at room temperature. 2+ Pre-adsorb, remove, and wash with deionized water;
[0057] S3, soaking the pretreated AZ31 magnesium alloy negative electrode sheet in a deposition solution (a mixed solution of 0.03 mol / L Ca(NO3)2 and 0.018 mol / L NH4H2PO4) at room temperature for 24 h to obtain a magnesium negative electrode modified with a bioceramic film layer composed of dihydrate calcium phosphate and a small amount of calcium phosphate, taking it out, washing it with deionized water, vacuum drying it, and sealing it for later use;
[0058] The surface-modified AZ31 magnesium alloy negative electrode was assembled into a magnesium metal air battery with a 3.5wt% NaCl aqueous electrolyte and an air positive electrode with a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization, and hydrogen evolution corrosion tests were performed.
[0059] The surface-modified AZ31 magnesium alloy electrode was assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte, and an AC impedance test was performed after standing for 1 hour.
[0060] Comparative Example 3
[0061] The AZ31 magnesium alloy negative electrode without surface modification was assembled into a magnesium metal air battery with a 3.5wt% NaCl aqueous electrolyte and an air positive electrode with a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization and hydrogen evolution corrosion tests were performed.
[0062] An AZ31 magnesium alloy electrode without surface modification was assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte, and an AC impedance test was performed after standing for 1 hour.
[0063] Comparative Example 4
[0064] A method for preparing a bioceramic film layer of an AZ31 magnesium alloy negative electrode of a magnesium-air battery comprises the following steps:
[0065] S1, cutting the AZ31 magnesium alloy sheet into several electrode sheets of 30 mm × 60 mm × 0.5 mm, polishing them with water-abrasive sandpaper (120#, 360#, 600#, 1200#) in sequence, then washing them with distilled water, and finally ultrasonically cleaning them in anhydrous ethanol for 10 min, and then drying them with cold air to use them as magnesium negative electrodes of magnesium-air batteries;
[0066] S2, the AZ31 magnesium alloy electrode with a cleaned surface was immersed in a supersaturated solution of Ca(OH)2 for 12 h at room temperature. 2+ Pre-adsorb, remove, and wash with deionized water;
[0067] S3, using a mixed solution of 0.03mol / L Ca(NO3)2 and 0.018mol / L NH4H2PO4 as the electrolyte, the treated AZ31 as the cathode, and a saturated KCl electrode as the anode, the electrodeposition was carried out in a constant voltage mode, the voltage was set to 3V, and the deposition was carried out at room temperature for 4h to obtain a magnesium negative electrode modified with a bioceramic film layer composed of dihydrate calcium phosphate and a small amount of calcium phosphate, which was taken out, washed with deionized water, vacuum dried, and sealed and packaged for use;
[0068] The AZ31 magnesium alloy negative electrode modified by electrochemical deposition was assembled into a magnesium metal air battery with a 3.5wt% NaCl aqueous electrolyte and an air positive electrode with a MnO2 catalyst. After standing for 1 hour, constant current discharge, negative electrode utilization and hydrogen evolution corrosion tests were performed.
[0069] The AZ31 magnesium alloy electrode with surface modification by electrochemical deposition was assembled into a three-electrode system with a saturated calomel reference electrode, a platinum sheet auxiliary electrode and a 3.5wt% NaCl aqueous electrolyte, and an AC impedance test was performed after standing for 1 hour.
[0070] The comparison results of the embodiments and comparative examples show that:
[0071] Figure 1 The photos are of the magnesium negative electrodes of the magnesium-air batteries in Comparative Example 1-3 and Example 1-3 after being discharged for 12 hours;
[0072] It can be seen from the pictures that by adopting the negative electrode modification method of the present invention, the degree of corrosion on the surface of the magnesium negative electrode is significantly reduced, indicating that hydrogen evolution corrosion is suppressed.
[0073] Figure 2 The optical photograph (a) and scanning electron microscope image (b) of the magnesium negative electrode in Example 2, and the scanning electron microscope image of the magnesium negative electrode of the magnesium-air battery in Example 2 (c) and Comparative Example 2 (d) after discharge for 12 hours;
[0074] It can be seen from the pictures that a bioceramic film layer of calcium hydrogen phosphate dihydrate is formed on the surface of the magnesium negative electrode in Example 2, and the film layer is composed of scaly crystals with a length and width of 20 to 50 μm; it can be further seen from the scanning electron microscope images (c, d) of Example 2 and Comparative Example 2 that after 12 hours of discharge, the corrosion pits on the surface of the WA111 alloy negative electrode without surface modification are larger and deeper than those on the WA111 alloy negative electrode surface modified by the method of the present invention, and the corrosion is obviously more serious.
[0075] Figure 3 The AC impedance diagrams of the magnesium electrodes in Comparative Example 1-3 and Example 1-3 after being immersed in 3.5wt% NaCl aqueous electrolyte;
[0076] from Figure 3 It can be seen that the AC impedance diagrams in Comparative Examples 1-3 and Examples 1-3 are composed of two capacitive reactance arcs located in the high-frequency and medium-low-frequency regions and an inductive reactance arc in the low-frequency region. The larger the capacitive reactance semicircle, the greater the impedance of charge migration and the better the corrosion resistance of the electrode. It can be seen that the negative electrode surface modification method of the present invention can improve the corrosion resistance of the magnesium negative electrode.
[0077] Figure 4 It is a graph of the hydrogen evolution rate of the magnesium negative electrode of the magnesium-air battery in Comparative Example 1-4 and Example 1-3 when discharged for 12 hours.
[0078] from Figure 4 It can be seen that the negative electrode modification method of the present invention can significantly inhibit the hydrogen evolution effect on the surface of the magnesium negative electrode, and the effect is better than the electrodeposition method in Comparative Example 4.
[0079] Figure 5The discharge specific capacity and negative electrode utilization of the magnesium-air battery in Comparative Example 2 and Example 2 at different current densities for 12 hours.
[0080] from Figure 5 It can be seen that compared with Example 2, the magnesium-air battery assembled with the surface-modified negative electrode exhibits a high discharge specific capacity (1237 mAh / g for the example and 603 mAh / g for the comparative example) and utilization rate (56.5% for the example and 27.5% for the comparative example).
[0081] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for modifying the surface of a magnesium negative electrode of a magnesium-air battery, comprising the following steps: S1: Cut the magnesium sheet into a number of electrode sheets of a certain size, polish them with sandpaper, then wash them with distilled water, and finally ultrasonically clean them in an organic solvent. After drying, they are used as magnesium negative electrodes of magnesium-air batteries. S2: The surface of the magnesium negative electrode was polished and cleaned at room temperature. The magnesium negative electrode was immersed in a supersaturated solution of Ca(OH)2. 2+ Pre-adsorb, remove, and wash with deionized water; S3: Soak the pretreated magnesium negative electrode in a mixed solution of 0.03-0.08 mol / L calcium salt and 0.015-0.05 mol / L dihydrogen phosphate at room temperature to obtain a magnesium negative electrode modified with a bioceramic film layer whose main component is calcium hydrogen phosphate dihydrate, take it out, wash it with deionized water, vacuum dry it, and seal it for later use.
2. A method for surface modification of magnesium negative electrode of magnesium-air battery according to claim 1, characterized in that: The size of the magnesium negative electrode sheet cut in step S1 is 30 mm×60 mm×0.5 mm.
3. A method for surface modification of magnesium negative electrode of magnesium-air battery according to claim 1, characterized in that: The model of the water-abrasive sandpaper used in step S1 is selected from 120#, 360#, 600#, and 1200#.
4. The method for surface modification of magnesium negative electrode of magnesium-air battery according to claim 1, characterized in that: The organic solvent used in step S1 is selected from volatile solvents such as anhydrous ethanol and acetone.
5. The method for surface modification of magnesium negative electrode of magnesium-air battery according to claim 1, characterized in that: The magnesium sheet used in step S1 is selected from a pure magnesium sheet and a magnesium alloy sheet.
6. A method for surface modification of magnesium negative electrode of magnesium-air battery according to claim 1, characterized in that: In step S3, a mixed solution of calcium salt and dihydrogen phosphate can be used as the electrolyte, the treated magnesium negative electrode is used as the cathode, and the anode is a saturated KCl electrode. The electrodeposition is carried out in a constant voltage mode, the voltage is set to 3V, and the deposition is carried out at room temperature for 4 hours to obtain a magnesium negative electrode modified with a bioceramic film layer whose components are dihydrate calcium hydrogen phosphate and a small amount of calcium phosphate.
7. A method for surface modification of magnesium negative electrode of magnesium-air battery according to claim 1 or claim 6, characterized in that: The calcium salt can be selected from Ca(NO3)2, CaCl2.
8. A method for surface modification of magnesium negative electrode of magnesium-air battery according to claim 1 or claim 6, characterized in that: The dihydrogen phosphate is selected from KH2PO4 and NH4H2PO4.
9. A magnesium negative electrode for a magnesium-air battery, characterized in that: The magnesium-air battery magnesium negative electrode is prepared by the surface modification method of the magnesium-air battery magnesium negative electrode according to claim 1.